The World Bank research program 1998 : Abstracts of current studies - World Bank (The World Bank, 1998)
The four basic objectives of the World Bank's research program are:broadening understanding of development; assisting in developing research capacity in member countries; improving the Bank's capacity in advising members; and supporting all aspects of its own operations. The report is the annual compendium of current Bank research. The abstracts in this volume report on research projects within FY98, describing questions addressed , analytical methods used, findings to date, and policy implications. In addition, each abstract identifies the expected completion date and the research team, as well as any report or publication produced. The abstracts cover 193 research projects grouped under nine major headings, as follows:1) poverty and social welfare; 2) labor markets and education; 3) environmentally sustainable development; 4) infrastructure and urban development; 5) macroeconomics; 6) international economics; 7) domestic finance and capital markets; 8) transition economies; and 9) private sector development and public sector management. An appendix is included, listing reports and publications produced by Bank research with corresponding availability sources. Abstracts are indexed by the sponsoring unit